Trastorno de depresión y su influencia en el desarrollo emocional de una persona de 22 años de la ciudad de Milagro - Garcia Zurita, Julissa Elizabeth (2022)
The present case study has been developed with the purpose of evaluating the severity of depression in a 22-year-old person from the city of Milagro, in which practical theoretical knowledge that was acquired during the process of learning psychology is present. clinic with the purpose of knowing the most affected aspects when suffering from this disorder. Consequently, Depression Disorder is one of the most common disorders today, which affects not only the person who is suffering from it, but also the people closest to him/her. It is reflected with symptoms of deep sadness, stomach problems, insomnia, discomfort in the body, withdrawal among others. The consequences can be serious if it is not controlled in time, because a person with severe depression can even have suicidal thoughts. Therefore, in the following case study, we worked with techniques such as: psychological interviews, clinical history, clinical observation, and with the application of tests: Beck Depression Inventory, Hamilton Anxiety Scale and Zung Depression Scale, the used to obtain a presumptive prognosis. From the cognitive behavioral therapy approach, therapy that was chosen for the psychotherapeutic intervention, in which four techniques were chosen, which were very helpful for the patient to understand the negative thoughts that were affecting him in his day to day, work in them also having positive thoughts and in this way continue improving their quality of life.